Analysis of the Influence of Audio Visual Media in Increasing Student Motivation and Learning Outcomes in Islamic Education and Character Subjects (Field Study of PAI and Character Learning at SMPN 2 Blora) - Dwi Bagus Santoso Setiawan; Wachidi; Hafidz (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The aim of this research is the influence of the use of audio-visual media in increasing motivation and learning outcomes in PAI and Character Education at SMPN 2 Blora. Education is an effort to develop the potential and talents of students and must be carried out with planned and conscious efforts to make it happen in accordance with educational goals. To achieve maximum learning results, one of the learning strategies is using audio-visual media. This media will make learning more effective, interesting and not boring. The development of audio-visual media in learning has been widely used by PAI teachers in schools. There are various forms, including audio only, visual only or a combination of both in the form of moving films. Learning methods using audio-visual media will encourage changes in the role of teachers as centers of information in learning. If teachers are good at using audio-visual media in the learning process, it will influence student motivation and learning outcomes, both visual, auditory and kinesthetic. Effectiveness of using audio media. This visual will create learning motivation and student learning outcomes in Islamic Education and Character subjects at SMPN 2 Blora.